Measuring Race and Ethnicity - Davis, Larry E.; Engel, Rafael J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Racial and ethnic issues stand at the core of social, political, and economic concerns in an increasingly diverse America. Accordingly, how individuals from the various ethnic groups regard themselves$1 (Band others$1 (Bis a salient focus of research studies across the disciplines. Measuring Race and Ethnicity gathers psychological measures of common phenomena such as racial identity, acculturation, and intra- and intergroup relations enabling researchers to compare concepts across groups and better evaluate differences and disparities. Most of the instruments date from the 1990s and later, while a number of still-useful earlier scales are included. Taken together, these tools strengthen a wide evidence base, and point to areas where new scales are warranted. Included in this volume: -Fourteen measures for African Americans, such as the Rejection Sensitivity Race Questionnaire and the Cultural Mistrust Inventory -Nine Caucasian-specific instruments, including the Race and Politics Survey and the Being White in America Scale -Nineteen acculturation scales for Latinos, some specific to Puerto Ricans, Cubans, and Chicanos -Eight Asian/Pacific Islander measures, including the Race-Related Stressor Scale and the Intergenerational Congruence in Immigrant Families Scale. -The Native American Acculturation Scale -Twenty-two generic measures, including the Experience of Discrimination Scale and the Scale of Ethnocultural Empathy Researchers in psychology, social work, and public health examining cultural and race-related topics will find an immediately relevant source of valid and reliable scales in Measuring Race and Ethnicity.s
Asian and Pacific Islanders.-Hispanics -- African Americans -- Caucasians -- Native Americans -- Generic.
Keywords: Philosophy (General).; Consciousness; Psychology; Personality and Social Psychology